Insect Management for Sweet Potatoes: ENY473/IG159, 9/2020 - Martini, Xavier; Webb, S. E. (EDIS, 2021)
Sweet potatoes, both orange- and white-fleshed varieties, are widely grown in Florida. Foliar pests, leafminers, whiteflies and armyworms, are generally not difficult to manage; in fact insecticides should be avoided to conserve their natural enemies. More serious are those pests whose immature stages feed on roots: sweetpotato weevil, wireworms, banded cucumber beetles, pale-striped and sweetpotato flea beetles, and in south Florida, Diaprepes weevils and white grubs.